PENERAPAN MODEL DISCOVERY LEARNING DENGAN BANTUAN MEDIA YOUTUBE PADA CHANNEL INSPECT HISTORY UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI DI MA MUHAMMADIYAH PEKANBARU - Ramadayani, Nori; Bunari, Bunari; Al-Fiqri, Yanuar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low interest in learning students in history subjects af class XI at MA Muhammadiyah Pekanbaru. Based on the findings related to the low interest in learning students, this study aims to determine teacher activities, student activities, and student learning interest through the application of the Discovery Learning model with the help youtube media on the Inspect History channel in class XI MA Muhammadiyah Pekanbaru. The research method used in this study is Classroom Action Research (CAR) and the research instrument used is the Teaching Module. The results of the study show that Teacher Activities in cycle I obtained an average value of 58% (sufficient) and increased in cycle II where Teacher Activities in cycle II obtained an average value reaching 80% (very good). Meanwhile, for student activities in cycle I obtained an average value of 55,5% (sufficient) and increased in cycle II to 74% with (good). On the other hand, student learning interest in cycle I obtained an average value of 69% (not successful), then increased in cycle II with an average value reaching 86% (success). Based on the research data obtained from the accumulation of teacher activity observation sheets, student activity observation sheets, and student learning interest questionnaires in cycle I and cycle II, it can be concluded that the application of the Discovery Learning model with the help of youtube media on the Inspect History channel can increase students’ interest in learning history subjects in class XI at MA Muhammadiyah Pekanbaru.